Vaginal Atrophy following Long-Term Depot Medroxyprogesterone Acetate Use: A Case Report - Christie Walker; Shawky Z. A. Badawy (Case Reports in Obstetrics and Gynecology)
Depot medroxyprogesterone acetate (DMPA) is a commonly used form of contraception, with noncontraceptive benefits for the user. The mode of action is through the suppression of ovulation. It leads to hypoestrogenism which causes dryness of the vagina and dyspareunia. We present in this paper a patient that was very symptomatic with regard to vaginal atrophic changes determined by vaginal cytology. This side effect may become increasingly more common as we see more long-term use of DMPA.